1993
DOI: 10.1007/bf00157398
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic pharyngeal carriage of beta-haemolytic streptococci and streptococcal pharyngitis among patients at an urban hospital in Croatia

Abstract: In a one-year study at the University Hospital of Infectious Diseases in Zagreb, Croatia the rate of asymptomatic throat carriage of beta-haemolytic streptococci was investigated. Throat carriage was investigated in 1796 patients, none of whom had a sore throat nor signs and/or symptoms of a respiratory tract infection. The carrier rate of beta-haemolytic streptococci was 8.3%, for group A streptococci 6%, group B 1.3%, group C 0.3% and group F 0.1%. The highest rate was observed in the 6 to 14 year age group:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
5
28
1
3
Order By: Relevance
“…Some studies (3,5,12) have reported no seasonal variation in prevalence of BHS in healthy individuals, but no comparison of prevalence of BHS in age-matched patients was done.…”
Section: Seasonal Variationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies (3,5,12) have reported no seasonal variation in prevalence of BHS in healthy individuals, but no comparison of prevalence of BHS in age-matched patients was done.…”
Section: Seasonal Variationmentioning
confidence: 99%
“…However, not all patients with a positive microbiological test for GABHS and symptoms from the throat have a GABHS-caused tonsillopharyngitis. Some of these patients may have a virus infection and are only carriers of GABHS (1,(3)(4)(5). and may not benefit from treatment with antibiotics at that time (4,6).…”
mentioning
confidence: 99%
“…Group C and G Streptococci are reportedly common causes of tonsillitis or pharyngitis in both adults and children in tropical countries [8,9,11] while group A is common in the temperate countries [29]. Other streptococcal groups of D, F and G isolated in this study have previously been implicated in tonsillitis [30]. [31] isolated streptococci groups A, B, C, G and a group called non-group A, B, C, D. This latter group may be likened to the UID group in our study.…”
Section: Discussionmentioning
confidence: 70%
“…The previous studies reported carrier rates of pneumococci in children as 2-10 % in Italy, 21-23 % in the USA, 20-70 % in Asia [25] and for the carrier rates of BHS: 8 % in Croatia and 16 % in India [26,27]. One meta-analysis study reported that the pool prevalence of group A streptococcus (GAS) carriage in children of all ages was 12 % (95 % CI 9-14 %) [28].…”
Section: Discussionmentioning
confidence: 93%